El método Montessori como estrategia pedagógica en la enseñanza de la lecto-escritura en aulas inclusivas (2020)
The research work arose from the need to work with children who have some special educational need and are part of inclusive classrooms, which gave rise to go hand in hand with the Montessori method as a primary basis for the strengthening of literacy in primary basic education. For this reason, it was inquired about the teaching methodologies used by teachers for the development of competences in first grade students of the Don Bosco Social Center Educational Institution, recognizing the lack of strategies to achieve inclusion in the classrooms. For this reason, this research sought to build strategies that help the educational work of teachers and strengthen reading-writing skills in inclusive classrooms, in order to establish meaningful learning in the cognitive and affective spheres of students, favoring their processes and becoming a pedagogical instrument to support educational practices. The research was approached from the socio-critical paradigm, using an qualitative investigative approach and makes use of the descriptive method. According to the methodological process developed, various techniques were included such as documentary analysis, questionnaire, survey and interview. Therefore, the results presented in the research were sufficient to achieve the objectives present in the study, ending with the conclusions and recommendations for future research related to the subject.